Land suitability evaluation of abandoned tin-mining areas for agricultural development in Bangka Island, Indonesia - A Asmarhansyah; Rodrigo B Badayos; Pearl B Sanchez; Pompe C Sta Cruz; Leonardo M Florece (Journal of Degraded and Mining Lands Management, 2017)
Kepulauan Bangka Belitung, Indonesia is one of the tin mineral-producer in the world. Agricultural crops could be a wise option for the reclamation since abandoned tin-mining lands have a high potency to be used as agricultural lands. This study was aimed to evaluate of the land/soil characteristics of abandoned tin-mining areas and to establish land suitability of the land area for agriculture used to formulate   appropriate   land   development measures and amelioration  strategies for  utilization of mined  areas  for crop  production. The land evaluation was conducted by comparing the land characteristics in every type of abandoned tin-mining areas with its crop requirements. The current suitability showed that in general  food crops, vegetable crops, fruit crops, and industrial crops were consider as not suitable (N). Spice and medicinal crops [pepper (Piper nigrum L.) and citronella (Andropogoh nardus L. Rendle)] were consider as not suitable (N), while the Jatropha (Jatropha curcas L.) and Kemiri Sunan (Aleurites moluccana  L. Willd) crops were considered as marginally suitable (S3) in abandoned tin-mining areas. The forest crops and forage crops were considered as marginally suitable (S3). The water availability, soil texture, and low soil fertility were considered as the limiting factors of all crops to get optimum production. For agricultural development, the soil physical and chemical properties of abandoned tin-mining land must be improved through integrated farming.